All Days 2010
DOI: 10.2118/140619-ms
|View full text |Cite
|
Sign up to set email alerts
|

Managing Reservoir Uncertainty in Gas Field Development Using Experimental Design

Abstract: In a new field development, enormous time and energy are put in to identify and quantify both static and dynamic reservoir uncertainties. This could be very challenging when information is limited and not readily available. These data uncertainties vary from project to project depending on the quantity of reliable reservoir data acquired during the exploration and appraisal stage. The first step towards managing reservoir uncertainty in field development is to identify and quantify the key reservoir parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Experimental design is a structured method used to evaluate relationship between the different factors affecting a process to the output of the process. It is widely used in statistics study, but also in petroleum engineering study as shown by Itotoi et al (2010) and Kalla, White, et al (2005). Among different method of experimental design, the one which is widely used in Oil and Gas engineering is the Full Factorial Design.…”
Section: Figure 1 P Ield Pipeline Network Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental design is a structured method used to evaluate relationship between the different factors affecting a process to the output of the process. It is widely used in statistics study, but also in petroleum engineering study as shown by Itotoi et al (2010) and Kalla, White, et al (2005). Among different method of experimental design, the one which is widely used in Oil and Gas engineering is the Full Factorial Design.…”
Section: Figure 1 P Ield Pipeline Network Mapmentioning
confidence: 99%
“…Bose and Kishen (1940) and Plackett and Burman (1946) provide information on how to de ine combination of factors in order to properly evaluate the relationship between them. Itotoi in his publication "Managing Reservoir Uncertainty in Gas Field Development Using Experimental Design" (Itotoi et al, 2010) demonstrate how to use experimental design to calculate the probability of Connected Gas In Place (CGIP) and Estimated Ultimate Reserves (EUR). The idea is using experimental design method to create a set of simulation inputs resulting in a response equation.…”
Section: Figure 1 P Ield Pipeline Network Mapmentioning
confidence: 99%
“…As part of his work he also explored the applicability of different regression equations to characterize reservoir models. Kabir et al (2004) and Itotoi et al (2010) also demonstrate experimental design applied to the development of green conventional fields using D-optimal and folded Plackett-Burman designs. Experimental design has also found applicability for fracture design, nodal analysis, and geostatistics [Zhang and Du (2011), Okenyi and Emeka (2012), White et al (2001), Friedmann et al (2001)].…”
Section: Experimental Design Applied To Reservoir Studiesmentioning
confidence: 99%